Successful limb salvage after an iatrogenic femoral atrio-venous fistula: A case report - Paharudin, Mohd Abdul Rauf; Abdul Rahman, Mohd Norhisham Azmi; Othman, Ahmad Faidzal (The Editorial Committee of Annals of Vascular Diseases, 2014)
We reported a case of iatrogenic femoral AVF occurred during insertion of a femoral catheter. A primary repair to the femoral vein and a primary end-to-end anastomosis for femoral artery performed with a successful result.